Use of follicle‐stimulating hormone for the male partner of idiopathic infertile couples in Italy: Results from a multicentre, observational, clinical practice survey. (7th January 2020) - Santi, Daniele; De Vincentis, Sara; Alfano, Patrizia; Balercia, Giancarlo; Calogero, Aldo E.; Cargnelutti, Francesco; Coccia, Maria Elisabetta; Condorelli, Rosita A.; Dal Lago, Alessandro; de Angelis, Cristina; Gallo, Mariagrazia; Iannantuoni, Nicola; et al.
Abstract: Background: The management of male idiopathic infertility is heterogeneous. Although meta‐analyses reported the effectiveness on pregnancy rate, the real clinical impact of follicle‐stimulating hormone (FSH) was not evaluated so far. In Italy, FSH is approved by the National Medicines Agency (AIFA) for idiopathic infertile patients with FSH < 8 IU/L, independently of semen parameters. Aim: Primary endpoint was to record the therapeutic approach to the male partner of infertile couples. Secondary aim was to assess changes of semen parameters during FSH treatment. Methods: A multicentre, prospective, observational, clinical practice survey was carried out, enrolling the male partner of infertile couples attending ten Italian participating centres. Inclusion criteria were as follows: couple infertility, age >18 years and FSH serum levels <8 IU/L. Thus, all men in which AIFA allowed the FSH prescription were enrolled. Primary endpoint was the number of infertile patients treated with FSH. Secondary outcomes were semen parameters. The treating physician decided whether to offer FSH therapy and whether to re‐evaluate the male partner. Results: A total of 718 infertile couples were enrolled, and 241 patients were re‐evaluated (median follow‐up: 4.5 months). In 64.9% (466 patients), a treatment was prescribed. FSH was prescribed in 397 patients (85.2% of treated men). Sperm concentration ( P  = .002) and normal form percentage ( P  < .001) significantly improved during FSH administration. No correlation was found between these parameters and FSH duration ( P  = .545 and P  = .627, respectively) or dosage ( P  = .455 and P  = .533, respectively). Among patients treated with FSH, the incidence of oligozoospermia decreased from 73.0% to 56.0% ( P  < .001) and teratozoospermia from 43.6% to 27.7% ( P  < .001). Discussion: This first nation‐wide survey reveals a FSH prescription rate of 55% in patients qualifying for treatment according to AIFA. Although the study was not designed to highlight FSH efficacy in male infertility, a slight increase in semen parameters was demonstrated in about half of the treated men without adverse events.